Study of interaction between cationic surfactant (CTAB) and paracetamol by electrical conductivity, tensiometric and spectroscopic methods - Nabi, Arshid; Tasneem, Shadma; Jesudason, Christopher Gunaseelan; Lee, Vannajan Sanghiran; Zain, Sharifuddin Md (Elsevier, 2018)
The interaction of a hydrophilic drug, paracetamol with the cationic surfactant cetyltrimethylammonium bromide (CTAB) in an aqueous media has been investigated by using conductometric, tensiometric and spectroscopic methods. The critical micelle concentration (CMC) values have been determined by two different methods and both the methods yielded identical CMC values. The experimental data of conductance and surface tension have been correlated against temperature and concentration using standard relations. The pseudophase separation model has been adopted for calculation of various thermodynamic parameters such as standard free energy ΔGm 0, enthalpy, ΔHmic 0, and entropy, ΔSmic 0, of micelle formation. The increase in the micellization with rising temperature is attributed towards the prevailing hydrophobic-hydrophobic increased interactions between the surfactant-drug aqueous mixtures. From the surface tension data the interfacial parameters such as the maximum surface excess concentration, Γmax, standard Gibbs free energy of adsorption at the air/solvent interface, ΔGad 0, and the minimum surface area pre molecule, Amin, were evaluated. Moreover, fourier transform infrared analysis (FTIR) was carried out to estimate the possible interactions prevailing in the miceller systems.